69.9k views
5 votes
(HELP 10 POINTS) Find the difference. Write your answer in standard form.

(−2x2+3)−(3x2+4x−5)

2 Answers

5 votes

-5x² -4x +8

remove parentheses and collect terms.

(-2x² +3) -(3x² +4x -5)

= -2x² +3 -3x² -4x +5

= (-2-3)x² -4x +(3 +5)

= -5x² -4x +8

User Rbajales
by
4.9k points
6 votes

9514 1404 393

Answer:

-5x² -4x +8

Explanation:

Eliminate parentheses and collect terms.

(-2x² +3) -(3x² +4x -5)

= -2x² +3 -3x² -4x +5

= (-2-3)x² -4x +(3 +5)

= -5x² -4x +8

User Cesar Romero
by
4.8k points